State Control Rights versus the Customary Rights of the Indigenous Peoples of North Central Timor NTT: A Review of Legal Philosophy - T. Bastanta Tarigan; Sri Wahyu Handayani; Tedi Sudrajat (Mahesa Research Center, 2026)
The conflict between the State’s Right of Control (Hak Penguasaan Negara) and customary land rights (hak ulayat) in Timor Tengah Utara (TTU), East Nusa Tenggara, Indonesia, represents a fundamental legal-philosophical tension. This study employs a normative-qualitative approach with conceptual and hermeneutical analysis to examine the ontological, epistemological, and axiological dimensions of the dispute. The findings reveal three layers of conflict: ontologically, the state’s right is public-functional while ulayat is sacred-collective; epistemologically, the state prioritizes written documents and cadastral maps, whereas the indigenous community relies on oral tradition and natural boundaries; axiologically, legal certainty, substantive justice, and utility clash, with identity recognition often neglected. The study concludes that resolving land conflicts in TTU requires an epistemic dialogue and binding customary deliberation (musyawarah adat-besar) that grants equal standing to traditional elders. Without mutual recognition between state and indigenous knowledge systems, agrarian justice remains unattainable.